REPLY TO: COMMENT TO: “VOLCANIC ACTIVITY FROM THE NEOGENE TO THE PRESENT EVOLUTION OF THE WESTERN MEDITERRANEAN AREA. A REVIEW” BY MICHELE LUSTRINO - Lustrino, Michele (Ofioliti, 2001)
We recently published a review of geochemical data on volcanic products emplaced during the last 30 Ma in the western Mediterranean area (Lustrino, 2000a). In this paper, the most recent petrogenetic models proposed for various igneous provinces were compared each other and tentatively fitted in a geodynamic scenario of evolution. The aim of that paper was to furnish an updated review of the petrologic models proposed to explain the origin of the main volcanic outcrops of Spain, France, Morocco and Italy, with special emphasis given to the Plio-Pleistocene volcanic rocks of Sardinia. The choice to focus on the recent volcanic activity of Sardinia was thought because of its geographic position (Sardinia represents a lithospheric slice in between two oceanic areas reworked during Hercynian and Alpine orogeneses), its peculiar trace element composition (Plio- Pleistocene volcanic rocks of Sardinia show the highest Ba/Nb and one of the lowest Ce/Pb and Nb/U among the entire Cenozoic European Volcanic Province anorogenic products) and its unique Sr-Nd-Pb isotopic signature (87Sr/86Sr close to bulk Earth values, eNd ~ -5, 206Pb/204Pb down to ~ 17; Lustrino et al., 2000).The comments of Elter seem to not take in consideration the true subject of our paper (geochemistry of 30-0 Ma volcanic rocks) and are entirely focused on the Hercynian geodynamic evolution of Western and Southern Europe. According to Elter, we presented a “continuous” model from Hercynian time to the present, but this is not the case. We don’t present any continuous model: on trace element and Sr-Nd-Pb isotopic grounds (data published elsewhere; Lustrino, 2000c; Lustrino et al., 2000) we simply suppose a relationship between processes responsible for the geochemical signature of mantle sources of Plio-Pleistocene volcanic rocks of Sardinia and those occurred in late Paleozoic, mainly during post-collisional extensional movements. Now we are going to reply to his doubts about the scientific valence of our paper (Lustrino, 2000a); in particular, we will follow its own scheme.